Case Report: Two cases of multiples and atypical dermal sinus tracts - Spazzapan, Peter; Thompson, Dominic N. P. (Frontiers in Pediatrics, 2024)
Dermal sinus tracts (DSTs) are congenital lesions that connect the cutaneous ectoderm with the underlying neuroectodermal tissues. They are typically midline, solitary lesions. Multiple, and atypically located DSTs have been only rarely described. We present two cases of multiple and laterally located DSTs. The first presented with bacterial meningitis and two tracts in the right buttock, one of which entered the spinal canal through the S3 neural foramen. The second child had three midline lumbar DSTs, one subcutaneous dermoid cyst and one intradural epidermoid cyst. Complete surgical excision was achieved in both cases with good late follow up. Multiple or atypically located DSTs appear to carry the same risks of infection as the more common, midline, single tracts. Complete surgical excision is recommended to avoid the risks of neurological deterioration, in particular due to infection. Incomplete disjunction is the proposed developmental anomaly for DSTs, however the location of the cases presented here requires an alternative explanation. Keywords 1. Dermal sinus tract 2. Infection 3. Tethered cord 4. Spinal dysraphism 5. Case reportThe parents gave permission for the University Medical Centre Ljubljana to publish the images present tin this study.